Transformasi Misi Bermodel Dialog ARIA: Dalam Perspektif Psikososial Komunitas - Rahayu, Rosa Damai (Perspektif, 2016)
Community life, taking the model of an Action-Reflection-Integration-Action dialogue within the socio-psychological perspective, explains and comprehends every individual in its personal complementarity, environment, and social actual context. Each action is reflected based upon its adaptation to the sources and happenings, which produces a new mission based on invention of sources and possibilities exist within the social network, creating conditions for raising potentials in empowering the present sources. The article argues that every missionary has become part of the event. It is precisely one of the requirements of religious life in today’s world. It is needed the power for controlling the various cultural and environmental transformation for sharpening the vision, new interpretation, respect, and intervention in the technoscientific inovation. Therefore, comprehension in controling technology might be managed as means and method of evangelization.